Personality-based learning as reflection of humanization of education - Kazakevych, Olena; Казакевич, Олена Ігорівна (Дніпровський державний аграрно-економічний університет, 2024)
In the article the problem of personality-based learning in the context of humanization of education is considered. The appropriatness of orientation to humanization and humanitarization of education is substantiated. It is established that humanization and humanitarization are interconnected with the solution of general problems of civilization that are of strategic importance for the development of not only education, but also humanity as a whole. It has been proved that humanization goes hand in hand with the humanitarization of higher education. The humanization of education undoubtedly means individualisation of the educational process. Historical background of personally-based learning is considered. У статті розглядається проблема особистісно орієнтованого навчання в контексті розглядається гуманізація освіти. Доцільність орієнтації на гуманізацію та обґрунтовано гуманітаризацію освіти. Встановлено, що гуманізація і гуманітаризація взаємопов'язані з вирішенням загальноцивілізаційних проблем, що мають стратегічне значення для розвитку не тільки освіти, а й людства в цілому. Це доведено, що гуманізація йде рука об руку з гуманітаризацією вищої освіти. Гуманізація освіти, безсумнівно, означає індивідуалізацію навчального процесу. Розглядаються історичні передумови особистісно орієнтованого навчання.
Особистісно орієнтоване навчання як відображення гуманізації освітнього процесу
Keywords: humanization and humanitarization in education; гуманізація і гуманітаризація в освіті; personality-based learning; особистісно орієнтоване навчання; innovative technologies in education; innovative technologies in education; personalized learning; персоналізоване навчання